Rupture uterus: a clinical analysis - Bandyopadhyay, Soma; Singh, Sipra (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Rupture uterus is one of the major causes of maternal mortality. It not only causes mortality, the survivor suffers much morbidity also. Finding out the etiology of rupture uterus, can help us to reduce its incidence. Present study is undertaken to know the scenario of rupture uterus in our institution. Methods: It is a retrospective study from 2011 to 2015. Data was obtained from the record section of the hospital. All rupture uterus cases were included. Previous mode of delivery, etiologies of rupture, operation performed etc. were studied. Results: Incidence of rupture uterus was 1 in 618 deliveries. Maternal mortality was 25%, perinatal mortality was 88.5%. Unbooked cases were 90.4%. Previous mode of delivery was vaginal delivery in 67.3% cases. Most common cause of rupture uterus was oxytocin overdose (26.9%) and handled labor (30.8%). Complete rupture was found in 75% cases. Subtotal hysterectomy was performed in 46.1% cases. Conclusions: Mandatory antenatal care (90.4% unbooked cases) and safe institutional delivery (oxytocin overdose and handled labor common cause) may change the rupture uterus scenario.